UPAYA PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PESERTA DIDIK MELALUI PENDEKATAN PROBLEM POSING BERBANTUAN QUIZIZ - Hakim, Abdul Hakim Ma'ruf; Husna, Nurina Aqmarina Husna (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to improve the quality of learning and increase the activity of students and the ability to solve mathematical problems of students through the Quiziz-assisted problem possing approach on Derivatives of Algebraic Functions. This research was carried out during the independent campus learning program in the form of teaching assistance learning in the education unit. Quiziz is used to make it easier for students to create and exchange questions with each other because learning is done online. This research method is classroom action research that follows the Kurt Lewin model. This study includes 3 cycles where each cycle includes 4 stages, namely planning, acting, observing, reflecting. The subjects of this study were 29 students in class XII-A of the DITKESAD Health Analyst Vocational School, while the data was collected through tests, interviews, and observations. The results showed that there was an improvement/increase in the quality of the implementation of learning, namely in cycle I of 79.38%, cycle II of 88.13% and cycle III of 91.88% and improvement/increase of student activity in cycle I of 69% , cycle II by 76%, and cycle III by 91%, and there was a significant increase in students' mathematical problem solving abilities as evidenced by the level of completeness of student learning outcomes in each cycle increased, namely in cycle I by 58.62%, cycle II of 75.86%, cycle III of 93.1%, and the results of interviews conducted concluded that learning mathematics using the problem-possing approach is fun for students. The conclusion that researchers can draw from this classroom action research is that learning mathematics using the problem-possing approach can improve the quality of learning and student activity as well as student learning outcomes. Keywords: solving math problems, problem possing, quiziz